Perkawinan Tungku Cu dari Manggarai, Flores Dalam Perspektif Hukum Kanonik Gereja Katolik - Jegaut, Siprianus (Perspektif, 2020)
The focus of this study is to discuss the Tungku Cu Marriage, the custom in Manggarai, Flores, in connection to Canon Law of the Catholic Church. The writer argues that Manggarai, as a social community, has invaluable cultural wealth that has shaped their character. One of the riches ofthis local culture is Kawing Tungku Cu (Tungku Cu Marriage). The custom is actually one of various forms of marriage in the Manggaraian society. Kawing Tungku Cu, however, becomes a dilemma when the Church has to deal with it in the light of the canon law. The writer argues that the purpose of every marriage is to continue the offspring and creativity of God himself. This study aims at finding the legal policy of the local Church in dealing with the Kawing Tungku Cu through literature studies and interviews. Finally, the writer suggests that pastoral workers are expected to have certain skills with regard to local culture; to build partnership; and to be able to create a close relationship between anak Rona and anak Wina.